Road Capacity Planning Based on Land Use (Case Study: Jalan Mr. Teuku Moh. Hasan West Side) - Hidayat, Agung Wahyudi; Fadhly, Noer; Caisarina, Irin (Journal of The Civil Engineering Student, 2022)
The determination of the batoh area as the new city center increased land user activities in the area so that there was also an increase in activities on the area's main road, namely Jalan Mr. Teuku Moh. Hassan. To find out the relationship between the development of land use in the area and the loading on the main road, it is necessary to know the factors that influence the increase in the burden on the road. To find out, the traffic volume and road capacity were calculated and modeling the trip generation and attraction caused by land users by dividing the layers for each area. Layer 1 is a commercial land use, while layers 2 and 3 are residential land use. For variables in commertial area, 3 variables were be calculated, while for residential areas 7 variables are thought to affect the burden. From the results, data processing was carried out and the capacity of the road was 2696,1 smp/hour. For the generation and pull data, multiple linear regression analysis was carried out using the backward method so that the modeling for layer 1 Y = 0.590 + 1,341 X3, for layer 2 Y = 0.220 +0.748 X1 + 0.828 X2 + 0.626 X3, and for layer 3 Y = -0.260 + 0.834 X1 + 0.720 X2 + 0.453 X3 + 0.225 X7.